In vivo imaging of porcine gastric enteric nervous system using confocal laser endomicroscopy &molecular neuronal probe. Issue 4 (April 2016) - Samarasena, Jason B.; Ahluwalia, Amrita; Shinoura, Susumu; Choi, Kee Don; Lee, John G.; Chang, Kenneth J.; Tarnawski, Andrzej S.
Abstract: Background and Aim: The gastric enteric nervous system (GENS) is organized into the submucosal plexus and the myenteric plexus that regulate muscle activity and mucosal functions, respectively. A non‐invasive, in vivo visualization of GENS was not possible until recent introduction of needle‐based confocal laser endomicroscopy (nCLE). Our aim was to determine the feasibility of in vivo visualization of GENS in the porcine stomach using endoscopic ultrasound (EUS) guided nCLE and local injection of molecular neuronal probe NeuroTrace. Methods: In anesthetized pigs during endoscopy, NeuroTrace was injected into the submucosa and muscularis propria of distal, and proximal stomach under EUS guidance and nCLE imaging was performed using the Cellvizio AQ Flex probe. After euthanasia, transmural gastric specimens from the areas of NeuroTrace injection were obtained for histology. We performed quantitative analysis of nCLE images recorded during in vivo studies: histologic evaluation of unstained specimens under fluorescence microscope for NeuroTrace localization. We also performed immunostaining of these specimens for nerve growth factor (NGF). In in vitro studies, we examined the uptake of NeuroTrace by glial cells. Results: The nCLE imaging successfully visualized neuronal cells and nerve fibers in distinctive image patterns. Fluorescence microscopy of mucosal sections showed that in vivo ‐injected NeuroTrace was retained in GENS components. NGF was strongly expressed in neural and glial cells, and the pattern of NGF staining was similar to that of NeuroTrace staining. Conclusions: This study demonstrates for the first time that combined use of EUS‐guided nCLE and NeuroTrace is capable to visualize GENS.